ResilienCity: Resilience and Psychotic-Like Experiences 10 Years After L’Aquila Earthquake - Rossi, Rodolfo; Socci, Valentina; Gregori, Eleonora; Talevi, Dalila; Collazzoni, Alberto; Pacitti, Francesca; Stratta, Paolo; Rossi, Alessandro; Di Lorenzo, Giorgio (Frontiers in Psychiatry, 2020)
An earthquake hit the city of L’Aquila in central Italy in 2009, leaving the city completely destroyed and 309 casualties. Unexpectedly, lower rates of psychotic experiences in persons affected by the earthquake compared to non-affected persons were found 10 months after the earthquake. The very long-term impact of a natural disaster on the prevalence of psychotic experiences deserves more in-depth detailing. The Authors examined resilience and psychotic experiences in a university student sample of 494. No effect of direct the earthquake (odds ratio = 0.64, 95%CI [0.37, 1.11]), material damages (odds ratio = 0.86, 95%CI [0.60, 1.23]), psychological suffering (odds ratio = 1.06, 95%CI [0.83, 1.36]) or global impact severity (odds ratio = 0.92, 95%CI [0.76, 1.12]) on psychotic experiences was detected. Resilience levels did not differ between affected and non-affected persons. Resilience showed a strong protective effect on psychotic experiences (odds ratio=0.38, 95% CI [0.28, 0.51]. The protective effect of the RSA factor “Perception of Self” was significantly stronger in individuals affected by the earthquake compared to non-affected subjects. Being affected by an earthquake is not a risk factor for psychotic experiences in a university student sample, as no direct effect of the earthquake was detected after 10 years after the event. Resilience is confirmed as a strong protective factor for psychotic experiences irrespectively of large collective traumatic events. Extension of these results to a general population sample could provide interesting insights into recovery from natural disasters.